POG03 Identification of a novel SCA 14 mutation in an Irish family. Issue 11 (22nd October 2010) - Albertyn, C; Murphy, R P; Rolfs, A; Lakhani, A
Abstract : Background: Spinocerebellar ataxia (SCA) type 14 is an autosomal dominant neurodegenerative condition associated with atrophy of the cerebellum and spinal pathways. Unlike the majority of SCAs, SCA 14 is not caused by CAG repeat expansions but by mutations in the protein kinase C gamma ( PRKCG ) gene. We describe a novel mutation of the PRKCG gene in a large Irish family. Case Description: Six affected family members are identified from two generations. The proband is a 43-year-old man with slowly progressive gait ataxia, mild dysarthria and limb incoordination. He describes intermittent involuntary jerky movements of his hands, suggestive of limb myoclonus. All affected members, including a 71-year-old woman, remain ambulant. Results of Investigations: Genetic testing for fragile X tremor ataxia syndrome and SCA 1, 2, 3, 6 and 7 was negative. A novel heterozygous mutation in the PRKCG gene (c.220 C>T) in exon 3 was found. The mutation is located in a highly conserved nucleotide and amino acid position with moderate physicochemical differences between histidine and tyrosine. Discussion: This is the first reported case of SCA 14 in Ireland. The clinical phenotype is in keeping with a mild, slowly progressive ataxic syndrome. Furthermore, a novel mutation in exon 3 of the PRKCG gene is identified.